Empirical Formulas of Shear Modulus and Damping Ratio for Geopolymer-Stabilized Coarse-Grained Soils - Wang, Shengnian; Gao, Xinqun; Ma, Wei; Li, Guoyu; Shi, Chong; Zhang, Peng (Frontiers in Physics, 2021)
The contributions of gravel fraction and cementation on the maximum shear modulus (Gmax), dynamic shear modulus ratio (G/Gmax), and damping ratio (λ) of cementitious coarse-grained soils have not been fully understood yet. Large-scale triaxial cyclic tests for geopolymer-stabilized coarse-grained soils (GSCGS) were conducted with different volumetric block proportions (VBP) under various confining pressures (CP) for investigating their dynamic behaviors and energy dissipation mechanisms. Results indicate that the Gmax of GSCGS increases linearly with VBP but nonlinearly with CP. High VBP will probably result in the G/Gmax decreasing gently and the normalized λ (λnor) growing rapidly, while the opposite is the case for a high CP. With the shear strain amplitude being normalized, the G/Gmax and λnor are distributed in a narrow band with low dispersion and thus can be well described by empirical functions of the normalized shear strain amplitude.